Phonetic disagreement in the most objectionable words in the Arabic dictionary: From the seventh century AH to the end of the thirteenth century AH - Abdel Hussein, Lamia; Naseem, Batoul (Al-Adab Journal, 2025)
The research deals with one of the lexicographic topics, which is the phonetic disagreement in the rejected words in the Arabic dictionary. It is a study drawn from a doctoral thesis. The study revealed the care of linguists in pointing out the rejected words. After investigation, it became clear that a number of words were mentioned in the Arabic dictionary. It contains substitution between fasts or vowels, and some scholars denied this substitution, which is what this study revealed.The study was divided into an introduction (the phenomenon of substitution in Arabic), and three axes. The first: it presented (the denial of substitution between vowels), the second: it included (the denial of substitution between vowels), and the third in which I studied (the denial of reasoning in the heart).